The Important Role of Learning Evaluation for Improving the Quality of Islamic Education: A Literature Study - Fatoni, Mahfud Heru; Subando, Joko (Jurnal Penelitian Pendidikan Islam, 2024)
The efficacy of Islamic education in fulfilling its objectives can be assessed by the evaluation of its graduates' outcomes. This study seeks to investigate the significant role of learning evaluation in enhancing the quality of Islamic education in schools. This study employs a library research methodology, gathering data from pertinent journals, articles, and books as reference materials. The data analysis methods employed were content analysis and thematic analysis. This study's findings demonstrate that learning evaluation plays a crucial role in enhancing the quality of Islamic education. Evaluations are conducted during the teaching and learning process to assess the effectiveness of teachers in conveying content and students' comprehension of the material presented. An extensive assessment of educational programs in schools is important. By means of thorough and ongoing assessment, educators can discern the strengths and weaknesses of pedagogical approaches, inspire students, and oversee their spiritual growth, while ensuring the internalization of Islamic values in their daily lives. This process aims to cultivate a generation that embodies not only intellectual acumen but also exemplary morals and integrity, thereby enhancing the quality of Islamic education.